Fabrication of high performance polypropylene based blends from ethylene vinyl acetate-based sole waste via solid-state shear Co-milling - Jian Yang; Wu Guo; Zhaogang Liu; Li Li (Polymer Testing)
Ethylene vinyl acetate copolymer (EVA) foam products with cross-linked structure are now widely used in the fields of functional footwear. However, due to their cross-linked structure and complex composition, they are quite difficult to be recovered in large scale after disposal, causing serious environmental pollution. Based on our self-designed solid-state shear milling (S3M) equipment, a novel co-milling technology was established to recycle ethylene vinyl acetate-based sole waste (ESW) and reuse it to strengthen and toughen polypropylene (PP). The effects of co-milling on PP/ESW powders as well as blends were studied, and the results showed that the existence of PP promoted the solid pulverization of ESW, so formed the powders with smaller size and wider distribution. Ascribing to the partial de-crosslinking of ESW during co-milling process, the contact area and the molecular entanglements at their interfaces increased, effectively improving the compatibility between PP and ESW. In this way, the simultaneous enhancement and toughening of ESW on PP were achieved. After co-milling, ESW phase in blends significantly decreased and no visible phase interface was observed. With 20 co-milling cycles, the tensile strength and impact toughness of PP/20 wt% ESW blend respectively increased from 21.9 MPa to 3.79 kJ/m2 to 25.4 MPa and 5.83 kJ/m2, both higher than most other similar PP based materials. This work provides a new strategy for high-quality and efficient recycling of ESW in large scale, and fabrication of high-performance PP based materials.